Issues and Prospects of Involvement of Economic Entities in the Process of Lifelong Learning in Russia - Galina TIMOKHINA; Irina SHIROCHENSKAYA; Evgeniya ZHADKO; Emil VELINOV; Inga KORYAGINA; Venera KADEROVA (Communications of International Proceedings, 2020)
This article attempts to systemize the results of existing research on the issues of lifelong education of adult population in Russia, based on the fragmented comparison of Russian education system with the lifelong learning system in Czech Republic to define key issues and opportunities for efficient engagement of main Russian economic entities in the lifelong learning process, namely adult population/households, training institutions and the state. The following desk research methods were used for study: content analysis and traditional analysis of data, collected in the framework of surveys of key entities involved in the process of lifelong education of adult urban and rural population in Russia in real time mode.  Based on data analysis the authors highlighted the problems and prospects of lifelong learning in the future for the main Russian economic entities for the purposes of improving the wellbeing of adult population in Russia. In particular, the authors identified potential opportunities for greater engagement of adult population in the process of lifelong learning; exposed factors, hindering the efficient management of adult lifelong education by corporate employers; demonstrated positive changes in the activity of institutions providing lifelong learning services to adults; detailed main functions of the state in further development of the system of lifelong learning in Russia.
Keywords: Research; Participants of Lifelong Learning Process.